A study on awareness and responsibility of residents in Klang, Selangor in an effort to reduce solid waste generation effectively - Karthigesu, Indrakaran T.; Syed Ismail, Sharifah Norkhadijah; Rasdi, Irniza; I., Fazizi; Kamaludin, (American-Eurasian Network for Scientific Information, 2014)
The main focus of this study is to create awareness among residents in district of Klang, Selangor to limit the generation of solid waste in a day. In addition, this study also aims to identify the level of awareness and responsibility of residents in district in an effort to reduce solid waste effectively. Overall, 120 respondents were involved in this cross sectional study. The respondents were selected randomly wherein involved majority of the local population. The instrument used in this study is questionnaire. The questionnaire consists of demographic components, determination item of awareness level and test on the level of responsibility towards environment. The respondents were male and female, multiracial, of various age groups, single as well as married, possessing the accepted level education from Penilaian Menengah Rendah to PhD, living in urban and rural residential areas featuring commercial, industrial or villages and residential types such as bungalow, terrace, condominium or squatting. Mean and standard deviation of the total items need to be studied as well as the acquired data for scores of awareness and responsibility. Data analysis using independent t test and one-way ANOVA were performed to observe the comparison between the level of awareness and the level of responsibility of respondents based on demographic factors. The results will show whether there is any significant difference or not (p> 0.05) for all the items studied. Next, the correlation test is done to find out whether there is a significant relationship between the levels of awareness with the responsibility of the respondents or not. Regression analysis was done to assess the level of responsibility when the level of awareness of the respondents increased. In conclusion, this study reflects that attitude as the main contributor to the uncontrolled generation of solid waste. Various programs can be planned and implemented. For instance, health promotion programs and recycling can be proposed to Local Authority in an effort to reduce solid waste. In addition, consultation methods can be applied to inculcate sense of love for the environment.